ANALYSIS OF THE RANGE OF HEAT-RETAINING INTERMEDIATE MATERIALS AND THEIR IMPACT ON ENERGY EFFICIENCY - Gaybullayeva, Nargiza Zayniddinovna (SCIENCE and SOCIETY, 2026)
This article provides a scientific analysis of the assortment of thermal insulation intermediate materials used in modern construction and their impact on energy efficiency. The study examines mineral, polymer-based, and natural thermal insulation materials, focusing on their physical and mechanical properties, thermal conductivity, and application areas.
Keywords: heat-retaining; intermediate materials; energy efficiency; thermal conductivity; building materials